Enhancing Digital Literacy in Inclusive IPAS Learning: Applying the TPACK Approach for Students with Disabilities in Elementary Schools - Muzaini, M Choirul; Fadhilah, Nurul; Khoiriyah, Zulfatul (Journal of Educational Research and Practice, 2025)
Despite the considerable potential for digital technologies in inclusive education, the exploration of TPACK pedagogies for the primacy of science in investigating students with disabilities is scant. This research aimed to implement TPACK for digital literacy and learning engagement in Ilmu Pengetahuan Alam dan Sosial (IPAS) instruction for students with hearing impairments and hyperactive verbalization in a state elementary school in Yogyakarta. The study employed a qualitative descriptive design, collecting data through classroom observations, semi-structured interviews with teachers, and document analysis. Findings indicate that teachers were able to modify IPAS content by using interactive videos that integrated sign language, visual simulations, and gamified applications to enhance student access and participation. This digital media provided clarity in conceptual understanding, thereby motivating students with diverse needs to engage actively in the inclusive classroom. This study provides evidence that a well-structured TPACK-based approach can facilitate the development of digital literacy while creating meaningful learning experiences for students with disabilities in primary schooling. Teacher preparedness, the availability of accessible digital resources, and the flexibility of pedagogical practices should, therefore, be emphasized to facilitate the successful implementation of TPACK-based practices in inclusive educational settings.